ANALISIS KEMAMPUAN BERPIKIR TINGGI SISWA PADA MATERI BILANGAN BULAT - Jumrawarsi, Jumrawarsi (STKIP Pesisir Selatan, 2021)
The purpose of this research was to determine the high order thinking skills of Students in SMPN 4 Pariaman. This research is a qualitative descriptive study. The research subjects consisted of 6 grade VII.1 students consisting of 2 high-ability, 2 moderate and 2 low-level students based on the score of assignments and daily tests from the mathematics teacher. Data analysis was in the form of analysis of students' test abilities, analysis ability in aspects of knowledge according to Bloom Taxonomy and interview analysis. The data validity test was done by using triangulation technique. The results of the test research show that the Bloom Taxonomic percentage of the increase with the average Bloom Taxonomy level of C4, C5, and C6 is 87.21%, 70.27%, 57.91%, respectively. This is the ability students have in solving problems that require higher-order thinking skills.